Defining the role of exposure to ACEs in ADHD: Examination in a national sample of US children. (February 2021) - Walker, Courtney S.; Walker, Benjamin H.; Brown, Dustin C.; Buttross, Susan; Sarver, Dustin E.
Abstract: Background: Clinical presentations of ADHD vary according to biological and environmental developmental influences. An emerging field of research has demonstrated relationships between exposure to adverse childhood experiences (ACEs) and ADHD prevalence, particularly in high-risk samples. However, research examining the combined role of traditional risk factors of ADHD and ACEs is limited, and reliance on high-risk samples introduces sampling bias. Objective: To examine the influence of ACEs on ADHD diagnosis using a large, nationally representative sample of US children. Participants and setting: Nationally representative samples (2017 and 2018) of 40, 075 parents from the National Survey of Children's Health (NSCH). Methods: We conducted logistic regression models to examine the association of ACEs and ADHD diagnosis, controlling for child and parent demographic variables and other risk factors. Results: Exposure to ACEs was significantly associated with parent-reported ADHD diagnosis, controlling for known parental and child-risk factors of ADHD. The association followed a gradient pattern of increased ADHD prevalence with additional exposures. Compared to children with no ACEs, the odds of an ADHD diagnosis were 1.39, 1.92, and 2.72 times higher among children with one, two and three or more ACEs. The ACE most strongly associated with the odds of ADHD was having lived with someone with mental illness closely followed by parent/guardian incarceration. Conclusions: Results further strengthen the evidence that ACEs exposure is associated with increased ADHD prevalence. Clinicians should assess ACEs in the diagnosis of ADHD. Furthermore, results of the study lend support to the efforts of agencies (both institutional and state-level) promoting routine screening of ACEs in children.